Lightweight batch authentication and privacy-preserving scheme for online education system. (December 2021) - Subramani, Jegadeesan; Nguyen, Tu N.; Maria, Azees; Rajasekaran, Arun Sekar; Cengiz, Korhan
Highlights: To ensure the data integrity, which is appropriately required for online education system (OES) during the exchange of information between the learners and examiners. Propose a computationally efficient authentication method to authenticate the batch of requests/messages received from the online batch learners. Propose a lightweight online batch message/material authentication method to authenticate the batch of messages/materials received from the examiner. To provide conditional privacy to OES users without revealing their actual identity in a resource-limited environment. Abstract: Nowadays, the online education system (OES) attracts learners to improve their knowledge and skills through learning flexibility and efficient assessment procedures. The learner can learn the courses and obtain a degree in a comfortable place, no need to go to school or college. Physical verification in the traditional education system is replaced by a secure authentication process. Many authentication schemes are existing to provide authentication, but they are suffering from authentication burden, due to high computational cost. In this work, two batch authentication schemes are introduced to validate the multiple learners and batch of messages/materials simultaneously instead of authenticating one after another. It reduces the authentication burden during the learner registration and message/material distribution process. The security and performance analysis sections ensures that the proposed scheme provides the essential security features with less computational costs compared to that of existing competitive schemes. Graphical abstract: Image, graphical abstract